Mononuclear Amido and Binuclear Imido Zirconium Complexes Supported by Dibenzotetraaza[14]annulene Ligands. X-ray Structure of [(Me(4)taa)Zr(andmgr;-NR)(2)Zr(NHR)(2)] (R = Bu(t) or 2,6-C(6)H(3)Me(2)). - Nikonov, G; Blake, A; Mountford, P (1997)
Reaction of 2 equiv of Li[NH-2,6-C(6)H(3)R(2)] with [(Me(4)taa)ZrCl(2)] (Me(4)taaH(2) = tetramethyldibenzotetraaza[14]annulene) gives the bis(amido) derivatives [(Me(4)taa)Zr(NH-2,6-C(6)H(3)R(2))(2)] [R = Pr(i) (1) and Me (2)]. Addition of Me(4)taaH(2) to [Zr(N-2,6-C(6)H(3)Pr(i)(2))(NH-2,6-C(6)H(3)Pr(i)(2))(2)(py)(2)] also affords 1. The reaction of 2 equiv of aryl or alkyl amines H(2)NR with the bis(alkyl) complex [(Me(4)taa)Zr(CH(2)SiMe(3))(2)] is the most versatile method for preparing [(Me(4)taa)Zr(NHR)(2)] (R = 2,6-C(6)H(3)Pr(i)(2), 2,6-C(6)H(3)Me(2), Ph, or Bu(t)). Reaction of 1 equiv of Me(4)taaH(2) with the binuclear complexes [(Bu(t)NH)(2)Zr(andmgr;-NBu(t))(2)Zr(NHBu(t))(2)] or [(py)(HN-2,6-C(6)H(3)Me(2))(2)Zr(andmgr;-N-2,6-C(6)H(3)Me(2))(2)Zr(NH-2,6-C(6)H(3)Me(2))(2)(py)] gives the asymmetrically substituted derivatives [(Me(4)taa)Zr(andmgr;-NR)(2)Zr(NHR)(2)] [R = Bu(t) (6) or 2,6-C(6)H(3)Me(2) (8)], which have been crystallographically characterized.